Luther's Radical Conception of Faith: God, Christ, and Personhood in a Post‐Metaphysical Age. (2nd September 2013) - Hansen, Guillermo
Abstract: Luther's exposition of Paul's letter to the Galatians offers a premier window into a deconstruction of the tandem God, ego and symbolic order of the law by proposing a radical "technology of the self, " a new understanding of what it means to be a person in light of God's own becoming in the flesh—a new subjective perspective. This places the event of belief as a displacement of a socially and ecclesiastically constructed ego‐consciousness and the emergence of a new (social) center of subjectivity—Christ consciousness, that is, faith. For Luther the "person" emerges as a radical break with the self‐referentiality of the ego and through the perspectival assimilation of God's own subjective experience in the flesh.